2012
DOI: 10.1136/bmjopen-2012-000897
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the impact of research on policy and practice: investigating the feasibility of using citations in clinical guidelines for research evaluation

Abstract: ObjectivesTo investigate the feasibility of using research papers cited in clinical guidelines as a way to track the impact of particular funding streams or sources.SettingIn recent years, medical research funders have made efforts to enhance the understanding of the impact of their funded research and to provide evidence of the ‘value’ of investments in particular areas of research. One of the most challenging areas of research evaluation is around impact on policy and practice. In the UK, the National Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…With a growing pool of research in this area, attention is moving toward the evolution of altmetric data relating to policy documents, and what policy makers could or should do with those data (Didegah et al, 2014). Funders should have a natural interest in such impact: if research they have supported is referenced as part of the evidence supporting a national and/or international clinical guideline, for example, then it is an indication that this research is likely to be influencing policy (Kryl et al, 2012). Until recently it was almost impossible to discover whether a piece of research had been cited in a policy document without either manually sifting through potentially relevant documents, by finding out through direct communication between the policy makers, or by pure chance.…”
Section: Altmetriccom Data and Policy Impactmentioning
confidence: 99%
“…With a growing pool of research in this area, attention is moving toward the evolution of altmetric data relating to policy documents, and what policy makers could or should do with those data (Didegah et al, 2014). Funders should have a natural interest in such impact: if research they have supported is referenced as part of the evidence supporting a national and/or international clinical guideline, for example, then it is an indication that this research is likely to be influencing policy (Kryl et al, 2012). Until recently it was almost impossible to discover whether a piece of research had been cited in a policy document without either manually sifting through potentially relevant documents, by finding out through direct communication between the policy makers, or by pure chance.…”
Section: Altmetriccom Data and Policy Impactmentioning
confidence: 99%
“…Clinical guidelines : Online clinical guidelines could be useful to assess the societal impact of individual medical studies by demonstrating their worth when deciding on general health care solutions (Kryl, Allen, Dolby, Sherbon, & Viney, ). A study of the cited references of clinical guidelines produced by the National Institute of Health and Clinical Excellence (NICE) in the United Kingdom found that articles cited in guidelines tend to be more highly cited than comparable articles (Thelwall & Maflahi, ).…”
Section: Sources Of Web Impactmentioning
confidence: 99%
“…Although a citation in clinical guidelines does not guarantee an impact on health, it demonstrates a peer perception of research utility and can be considered as an intermediate outcome [26]. Research by the Wellcome Trust, the Medical Research Council (MRC), and the NIHR demonstrated the feasibility of employing conventional bibliometric analysis of research papers cited on clinical guidelines to assess the impact of biomedical research on healthcare policy and practice [24,26,133]. …”
Section: Resultsmentioning
confidence: 99%